Wake Dynamics and Vortex Synchronization in Multi-Cylinder Arrays: A Computational Insight into Aerodynamic Performance and Flow Interference - Chamoli, Sunil; Mangrulkar, Chidanand K.; Uniyal, Anirudh; Bhatt, Mohit; Joshi, Nikhil; Rawat, Abhishek; Bhatt, Kapil; Pant, Pawan Kumar; Chuwattanakul, Varesa; Eiamsa-ard, Smith (My University, 2025)
This study presents a detailed computational investigation of unsteady laminar flow around two-dimensional square cylinders arranged in multiple configurations. Simulations were performed using ANSYS Fluent 2019 at Reynolds numbers ranging from 50 to 200, with three geometric layouts as follows: two vertically aligned cylinders, three inline cylinders, and three staggered cylinders. Center-to-center spacing ratios of 1.5D, 2.5D, and 3.5D were evaluated to assess wake interference, vortex shedding behavior, and aerodynamic force fluctuations. Results reveal that a close spacing (1.5D) causes strong wake coupling and highly irregular flow behavior, especially with inline configurations, leading to amplified drag and suppressed vortex shedding with downstream cylinders. In contrast, a staggered three-cylinder arrangement at 3.5D spacing exhibits regular vortex shedding, uniform force distribution, and minimized flow-induced oscillations, indicating aerodynamic stability. The Strouhal number, computed using FFT analysis, confirms the onset of periodic shedding at higher Reynolds numbers and highlights optimal synchronization at wider spacings. The study concludes that staggered configurations with appropriate spacing outperform inline setups in terms of flow control, dynamic stability, and reduced aerodynamic interference, offering insights relevant to high-rise building clusters and industrial heat exchanger design.
Keywords: CFD; laminar flow; Reynolds number; square cylinder; Strouhal number; vortex shedding; wake interaction